2019
DOI: 10.1080/15592294.2019.1646572
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes and assisted reproductive technologies

Abstract: Children conceived by Assisted Reproductive Technologies (ART) are at moderately increased risk for a number of undesirable outcomes, including low birth weight. Whether the additional risk is associated with specific procedures used in ART or biological factors that are intrinsic to infertility has been the subject of much debate, as has the mechanism by which ART or infertility might influence this risk. The potential effect of ART clinical and laboratory procedures on the gamete and embryo epigenomes heads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 122 publications
(144 reference statements)
2
55
0
2
Order By: Relevance
“…In both humans and mouse models, a hallmark of DNA methylation changes after ART is that it occurs to a greater extent in some infants than others. Some ''outliers'' are uniquely susceptible to the epigenetic disruptions of ART, and methylation differences are more pronounced when these groups are studied (1,3). Despite the current data, we still do not have a complete grasp on how newborns conceived by ART are affected and whether these changes persist into childhood or adulthood.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In both humans and mouse models, a hallmark of DNA methylation changes after ART is that it occurs to a greater extent in some infants than others. Some ''outliers'' are uniquely susceptible to the epigenetic disruptions of ART, and methylation differences are more pronounced when these groups are studied (1,3). Despite the current data, we still do not have a complete grasp on how newborns conceived by ART are affected and whether these changes persist into childhood or adulthood.…”
mentioning
confidence: 86%
“…The data to date exploring the effect of ART on deoxyribonucleic acid (DNA) methylation disruptions in newborns has been far from consistent. In multiple studies, DNA methylation changes have been observed in children conceived by ART, particularly when global DNA methylation has been assessed utilizing genome-wide assays (1). Although confounding factors such as age and infertility are likely contributory, the differences in methylation appear to be a consequence of ART itself and not simply because of underlying infertility (2).…”
mentioning
confidence: 99%
“…Some studies have suggested that ART procedures are also able to induce changes in methylation patterns in nonimprinted regions of the genome [ 82 , 86 , 87 ]. Moreover, this differential methylation occurs not only in the placenta but also in fetal tissues, and the changes appear to be tissue-specific [ 82 , 85 , 88 , 89 ]. However, an important question—are these alterations due to the ART procedures themselves or do they reflect the underlying infertility of the parents?—remains difficult to answer due to confounding factors in human studies.…”
Section: Epigenetics and Artmentioning
confidence: 99%
“…The effects of gestational age at birth on health outcomes may be linked to epigenetic patterns established in utero or early in the postnatal period [ 8 , 9 ]. Changes in these patterns may interfere with critical developmental processes [ 10 12 ] and trigger phenotypic changes that persist throughout life. This may be even more pertinent to children conceived by assisted reproductive technologies (ART), because ART procedures coincide with the extensive epigenetic reprogramming in the early embryo [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%